Reverse engineering and innovation: Empirical evidence from a high-tech economy - Kornelius Kraft; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
Reverse engineering allows firms to learn about critical components and design features of competitors' technologies. Historically, reverse engineering has often been used to help technological laggards to catch-up and profit from other's inventions. However, through reverse engineering firms may also obtain knowledge that can be used for own innovation efforts beyond mere imitation, making it a relevant knowledge acquisition channel for technological leading firms in high-tech economies. Based on data from the German part of the Community Innovation Survey (CIS), this paper provides empirical evidence on the characteristics of firms that use reverse engineering, and whether reverse engineering can lead to superior innovation performance in terms of commercializing innovations with a high degree of novelty. Our results suggest that in the context of a high-tech economy, it is rather firms that operate under fierce price competition that use reverse engineering, helping them to obtain higher innovation output, though for innovations with a low degree of novelty.
Keywords: O31; O33; D83; 330; Reverse engineering; knowledge spillovers; innovation output